Dinamika Praktik Perdagangan Saham dalam Perspektif Fatwa DSN-MUI: Investasi atau Spekulasi? - Muhammad Sauqi; Muhammad Noval Azkia; Muhammad Arief Budiman (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2026)
The development of the Islamic capital market in Indonesia shows increasingly complex dynamics along with the growing knowledge and participation of society in investment activities, particularly in stock investment. Advances in technology have made stock investment more accessible and attractive as an alternative for gaining profit and maintaining financial stability in the future. However, the growing practice of stock trading has raised debates among society regarding whether such activities contain elements of speculation prohibited in Islam. Therefore, this study was conducted to analyze the differences between speculation and investment practices in stock trading based on the perspective of DSN-MUI fatwas. This research uses a qualitative method with a literature study approach by examining relevant sources such as journal articles, books, and regulations related to the Islamic capital market. The results show that stock investment in Islamic perspective is not automatically categorized as maysir (gambling) as long as it is conducted with careful analysis, consideration of company performance, and a long-term investment orientation. Conversely, activities relying solely on price fluctuations without adequate analysis tend to lead to speculative practices resembling of gambling.